PML diagnostic criteria: Consensus statement from the AAN Neuroinfectious Disease Section - Berger, Joseph R. (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: To establish criteria for the diagnosis of progressive multifocal leukoencephalopathy (PML). METHODS: We reviewed available literature to identify various diagnostic criteria employed. Several search strategies employing the terms “progressive multifocal leukoencephalopathy” with or without “JC virus” were performed with PubMed, SCOPUS, and EMBASE search engines. The articles were reviewed by a committee of individuals with expertise in the disorder in order to determine the most useful applicable criteria. RESULTS: A consensus statement was developed employing clinical, imaging, pathologic, and virologic evidence in support of the diagnosis of PML. Two separate pathways, histopathologic and clinical, for PML diagnosis are proposed. Diagnostic classification includes certain, probable, possible, and not PML. CONCLUSION: Definitive diagnosis of PML requires neuropathologic demonstration of the typical histopathologic triad (demyelination, bizarre astrocytes, and enlarged oligodendroglial nuclei) coupled with the techniques to show the presence of JC virus. The presence of clinical and imaging manifestations consistent with the diagnosis and not better explained by other disorders coupled with the demonstration of JC virus by PCR in CSF is also considered diagnostic. Algorithms for establishing the diagnosis have been recommended.